Effectiveness of allopurinol on triglyceride levels in hyperuricemic patients - Žiga, Nermina; Bečić, Fahir; Dedić, Mirza (International Journal of Research in Medical Sciences, 2018)
Background: In this clinical pharmacological research, we dealt with the action of allopurinol on triglyceride levels in hyperuricemic patients. Methods: The study included 40 hyperuricemic patients, of both genders and different age groups, that were sorted by comorbid diagnoses in several subgroups. All patients were clinically treated in the period of three years both at UCC Sarajevo, and P.I. General Hospital "Abdulah Nakaš" Sarajevo. All clinical measurements were carried out using standard IFCC methods with the appropriate analysers. Results: The study was based on mean triglyceride levels before and after three and six months of treatment with allopurinol. It was found out that the mean triglyceride levels were not significantly different from the reference values prior to treatment (p = 0.846) and after three months of therapy (p=0.153). In contrast, after six months of treatment, triglyceride levels significantly increased compared to the reference values. In patients with a diagnosis of gout and metabolic syndrome, triglycerides were statistically significantly increased during the six months of observation. A statin group of patients showed a statistically significant increase in triglyceride levels after three months of therapy (p = 0.032), while, after six months their levels had decreased (p = 0.029). In patients with diabetes mellitus type II, triglycerides rose after three months of treatment (p = 0.039) and retained the same level after six months of observation. Conclusions: The analysis shows that the use of allopurinol has an effect on triglyceride levels in hyperuricemic patients.